Management of Tracking in Real Time on a Website-based Laundry Information System - Mastha Cahyaningrum, Dewi Pratama; Norhikmah, Norhikmah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Dewi Jaya Laundry provides a variety of laundry services. However, the administrative process and transactions with customers are still not computerized, so it can take more time and customers cannot do tracking of their clothes. To overcome these problems, a solution was built in the form of a website-based information system that has a Real Time Tracking feature. Primary data collection was obtained directly from the research site, namely Dewi Jaya Laundry located on Perumnas street by making direct observations at Dewi Jaya Laundry. Meanwhile, we gather secondary knowledge from scientific articles and books on database development for websites. It utilizes Waterfall research methodology and is built with PHP and MySQL databases. This system is built through the stages of analysis, design, development, and testing. The black box method is used for system testing, which emphasizes the functionality of the system. The system's ability to perform its intended functions has been verified by the test results. This research succeeded in developing a laundry information system that has a Real Time Tracking feature that functions to monitor customer laundry packages, so customers can know which stage of the washing or drying process is taking place, so they can know when clothes are ready to be taken.